Faktor Yang Berhubungan dengan Keluhan Musculoskeletal Disorders (Msds) pada Pekerja Konstruksi Pt. Pembangunan Perumahan di Bendungan Manikin - Titik Yuwantri Lady Suratno; Luh Putu Ruliati; Mustakim Sahdan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Occupational health problems can cause ergonomic hazards, namely Musculoskeletal Disorders (MSDs). Musculoskeletal complaints are complaints in the skeletal muscles that are felt by a person ranging from very mild to severe complaints. Initial research conducted on 10 workers, there were 7 who experienced MSDs complaints. The study was conducted on Manikin Dam construction workers to determine the factors associated with MSDs complaints. The type of research is analytic survey and cross sectional design. The population is 104 respondents with a sample of 51 respondents. Data was collected using interview, observation and measurement techniques. The study used the chi square test to see the relationship between the independent and dependent variables, and the multiple logistic regression test to determine the most significant variable associated with the dependent variable using the backward stepwise method. The results showed that the Manikin Dam construction workers experienced the most MSDs complaints in the upper neck and waist totaling 47 respondents (92.2%) and the least complaints on the buttocks amounting to 8 respondents (15.7%). The results of statistical tests, there is a relationship between age, years of service, smoking habits, work attitudes and workload with complaints of MSDs, while working hours, temperature and noise have no relationship with complaints of MSDs. It is hoped that the relevant agencies will pay attention to work attitudes. The work period of more than 2 years must be reduced by the workload. Workers who have a smoking habit, reduce cigarette consumption to maintain health and reduce the risk of MSDs.